Sialendoscopy for Improvement of Salivary Flow in Patients with Sjögren Syndrome - Comparative Analysis of Intraglandular Washing Solutions - Pascoto, Gabriela Robaskewicz; Gasparin, Andrese Aline; Piltcher, Otávio Bejzman; Kuhl, Gabriel; Cavazzola, Leandro Totti (International Archives of Otorhinolaryngology, 2020)
Introduction Among the potential diseases that present altered salivary flow and activity is Sjögren syndrome. Sialendoscopy seems to be an important therapeutic option.Objective To compare the results obtained with sialendoscopy for improving salivary flow measured by scintigraphy in patients with primary Sjögren syndrome to those obtained with other intraglandular washing solutions.Methods Patients from our institution's rheumatology clinic diagnosed with primary Sjögren syndrome underwent parotid scintigraphy prior to the sialendoscopy procedure. During the sialendoscopy procedure, one of the parotid glands was randomized to receive a wash with saline while the other was washed with a corticosteroid solution. After 1 month, a new scintigraphy examination of the parotid glands was performed to observe the salivary flow for comparison.Results A total of 13 female patients with mean age of 53.38 years (range, 27–76 years) were included in this study. After sialendoscopy, 10 patients (76.92%) were observed to have improvement in salivary excretion with radiopharmaceutical during scintigraphy. When analyzing each gland that was treated separately (26 glands), after sialendoscopy, improvement was observed in 18 glands (69.23%), 8 treated with dexamethasone and 10 with saline solution in the wash. There was no improvement in 8 glands (30.77%).Conclusion This study demonstrates that sialendoscopy is as an important tool to improve salivary flow measured by scintigraphy in patients with primary Sjogren syndrome, increasing salivary excretion through dilation and consequent unblocking of the ducts. These data suggest that there is no statistically significant difference between intraductal washing solutions using saline or dexamethasone solution.
Keywords: salivary flow; Sjögren syndrome; sialendoscopy; salivation; parotids